Prevalence of osteoporosis in schizophrenia patients using the osteoporosis self-assessment tool for Asians. (2nd January 2018) - Subramaniam, Aditya; Lim, Susan; Abdin, Edimansyah; Chong, Siow Ann
Abstract: Objective : The aims of the current study were to investigate the prevalence and socio-demographic correlates of risk of osteoporosis in Singapore among patients with schizophrenia using the osteoporosis self-assessment tool for Asians (OSTA). Method : Data for the current study was drawn from a clinical database maintained at the Institute of Mental Health Singapore. The OSTA index was used to calculate the risk for osteoporosis among those aged 50 years and above. Results : A total of 2569 patients were included in the study. About 34.6% met the criteria for osteoporosis using the OSTA cut-off of ≤ −1. Among the males 22.8% met criteria for high risk and 1.5% met criteria for very high risk, while among women 28.2% were at intermediate risk and 14.9% were at high risk of osteoporosis. The logistic regression analysis showed that older age and female gender were significantly associated with a higher risk of osteoporosis, while those with a history of hypertension and hyperlipidemia were less likely to be associated with a risk of osteoporosis. Conclusion : The OSTA could be a useful, inexpensive and quick tool to both identify those with osteoporosis as well as to measure the effectiveness of interventions meant to alleviate it.